A comparison of the film thickness of two adhesive luting agents and the effect of thermocycling on their microTBs to feldspathic ceramic. - Pereira, Priscilla C; Castilho, Anderson A; Souza, Rodrigo O A; Passos, Sheila P; Takahashi, Fernando E; Bottino, Marco A (My University, 2009)
The aim of the present study was to evaluate the effect of thermocycling (TC) on the microtensile bond strength (microTBS) of two luting agents to feldspathic ceramic and to measure their film thickness (FT). For the microTBS test, sixteen blocks (6.4 x 6.4 x 4.8 mm) were fabricated using a feldspathic ceramic, etched with 10% hydrofluoric acid, rinsed and treated with the silane agent. The ceramic blocks were divided into two groups (n= 8): Gr1: dual-cured resin cement and Gr2: flowable resin. The luting agents were applied on the treated surfaces. Microsticks (1 +/-0. 1mm2) were prepared and stored under two conditions: dry, specimens immediately submitted to the microTBS test, and TC (6,000 cycles; 5 degrees C-55 degrees C). The microTBS was evaluated using a universal testing machine (1 mm/min). The microTBS data (MPa) were submitted to two-way ANOVA and Tukey' test (5%). For the FT test (ISO 4049), 0.05 ml of each luting agent (n=8) was pressed between two Mylar-covered glass plates (150 N) for 180 seconds and light polymerized. FT was measured using a digital paquimeter (Model 727-2001). The data (mm) were submitted to one-way ANOVA. The luting cement did not influence the microTBS results (p= 0.4467). Higher microtensile bond values were found after TC (20.5 +/- 8.6 MPa) compared to the dry condition (13.9 +/- 4. 7MPa), for both luting agents. The luting agents presented similar film thicknesses: Gr1- 0.052 +/- 0.016 mm; Gr2-0.041 +/- 0.003 mm. The luting agents presented similar film thickness and microTBS values, in dry and TC conditions and TC increased the bond strength regardless of the luting agent.
Keywords: tooth cement; ceramics; comparative study; dental bonding; materials testing; temperature; Ceramics; Dental Bonding; Dental Cements; Materials Testing; Temperature